2020
DOI: 10.11604/pamj.2020.37.223.26418
|View full text |Cite
|
Sign up to set email alerts
|

Challenges with medical education in Nigeria in the COVID-19 era

Abstract: On March 20 th 2020 the Federal Government of Nigeria ordered the closure of all educational institutions, this was inclusive of all medical schools in the country. During the initial phases of this closure, most institutions were at a loss on how to proceed with learning as universities in Nigeria use mainly the didactic lecturing model. As the lockdown progressed it became imperative to the institutions to set up e-learning media for continued instruction of students. It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In this respect, several studies have discussed the challenges of social interaction in students. Accordingly, most students complain of the reduced depth and quality of learning, mentioning the neglected areas of virtual education, such as the lack of in-depth online conversations, lack of improvised and creative ideas, lack of understanding others and not being understood by others, lack of acquaintance with others, and lack of learning and having a behavioral and learning role model (11,13,15,19,22). Furthermore, the results obtained from the assessment of the articles revealed that most students attended online classes via smartphones.…”
Section: Student-related Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, several studies have discussed the challenges of social interaction in students. Accordingly, most students complain of the reduced depth and quality of learning, mentioning the neglected areas of virtual education, such as the lack of in-depth online conversations, lack of improvised and creative ideas, lack of understanding others and not being understood by others, lack of acquaintance with others, and lack of learning and having a behavioral and learning role model (11,13,15,19,22). Furthermore, the results obtained from the assessment of the articles revealed that most students attended online classes via smartphones.…”
Section: Student-related Challengesmentioning
confidence: 99%
“…Most students are willing to continue online classes owing to their experience of such courses during the pandemic (24). Other major challenges of virtual education were reported to be the lack of alternatives and asking students' opinions about whether they are willing to attend online classes (18), boring online lectures (19), low self-regulation of students in e-learning (17), low knowledge quality of students in e-learning classes (29), poor online content (11), not having a personal computer/laptop, and poor internet facilities (14).…”
Section: Student-related Challengesmentioning
confidence: 99%
“…The transition to e-learning and teaching services to bridge the learning gaps is, however, not seamless. 5 Factors such as inadequate funding to install and maintain as well as train staff to use the electronic interface, lack of internet access, frequent interruptions in power supply, and unavailability of individual computers for remote learning has slowed this transition. With these challenges militating against optimal education, coupled with restricted face-to-face learning prospects, the quality of medical education is on a downward trajectory with detrimental future implications.…”
Section: Adverse Learning Consequences Of the Pandemicmentioning
confidence: 99%
“…Ossai (2020) in his publication on the readiness of Nigeria to tackle the impact of COVID-19 on medical education also shared similar sentiments, stating further that the lack of funding and infrastructure not only made Nigeria ill-equipped to handle the challenges that arose for undergraduate medical education, but also for postgraduate medical education including residency training. 17 Many students attending these public institutions also felt that a quick transition from traditional lectures to online learning would prove difficult and ineffective as many claimed that lack of regular electricity supply and cost of internet subscription would hinder many students from attending online classes, the same reasons given in a publication by Oladipo et al (2020) addressing the challenges of medical education in the pandemic era. 18 Similar challenges were also stated in a study done in India 5 and a write up from Brazil 19 concerning the implementation of online learning in public institutions in the respective countries, which are both middle income countries like Nigeria.…”
Section: Integrative Learning Responses Of Medical Institutions and Student Bodies To Covid-19 Disruption Of Medical Educationmentioning
confidence: 99%
“…17 Many students attending these public institutions also felt that a quick transition from traditional lectures to online learning would prove difficult and ineffective as many claimed that lack of regular electricity supply and cost of internet subscription would hinder many students from attending online classes, the same reasons given in a publication by Oladipo et al (2020) addressing the challenges of medical education in the pandemic era. 18 Similar challenges were also stated in a study done in India 5 and a write up from Brazil 19 concerning the implementation of online learning in public institutions in the respective countries, which are both middle income countries like Nigeria. However, this was not the case for higher income countries such as the United States, 2 China, 3 and others 20 , who already had the infrastructure and systems for online learning and thus easily adapted even to the peculiar challenges of medical education.…”
Section: Integrative Learning Responses Of Medical Institutions and Student Bodies To Covid-19 Disruption Of Medical Educationmentioning
confidence: 99%